Correlation of Two Colposcopic Indices for Predicting Premalignant Lesions of Cervix - Kushwah, Sweta (J Midlife Health, 2017)
Cervical cancer is the second most common malignancy among women in India, mainly affecting the females of Peri-Menopausal age group. Colposcopy has been very useful for diagnosing cervical cancer to guide the biopsy. Reids and Scalzi proposed the Reids Colposcopic Index (RCI) to make colposcopic diagnosis less subjective, which is currently the most accepted scoring system. Recognizing the correlation of size of the lesion with likelihood of harbouring high grade disease, a new scoring system, the Swede score, has been devised by Strander et al in 2005. In present study we compared the Reids colposcopic index with Swede score. From the present study it is evident that Swede score of 8 or more has 100% specificity and can be used for performing direct excisional procedure as a “see-and-treat” method at this cut-off. This may be the preferred method for the treatment of high-grade CIN because it reduces the number of visits to the clinic and failure to receive treatment.